Pornography Consumption, Perceptions of Pornography as Sexual Information, and Condom Use. Issue 8 (17th November 2018) - Wright, Paul J.; Sun, Chyng; Steffen, Nicola
ABSTRACT: Pornography use is becoming more commonplace and may be a modality by which individuals receive sex education. This survey study assessed pornography consumption, perceptions of pornography as a source of sexual information, and condom use in a heterosexual sample of 200 sexually active German adults who were not in monogamous relationships. At the bivariate, overall sample level, there was only a modest association between consuming pornography and a decreased frequency of condom use. However, consistent with the sexual script acquisition, activation, application model (3 AM) of sexual media socialization, this association was moderated by differential perceptions of pornography as a source of sexual information. Interaction decomposition revealed that there was no association between pornography consumption and condom use among participants who disagreed that pornography is a source of sexual information. Conversely, pornography consumption was associated with a lower frequency of condom use among participants who agreed that pornography is a source of sexual information. As the perception that pornography is a source of sexual information strengthened, the relationship between pornography consumption and less frequent condom use increased. Gender did not moderate these associations. These findings point toward the importance of fostering a critical reading of pornography through media literacy education.